Independent associations of vitamin D metabolites with anemia in patients referred to coronary angiography: the LURIC study - Ernst, Jana Barbara; Kleber, Marcus E.; Grammer, Tanja B.; März, Winfried (European journal of nutrition, 2017)
Purpose: Anemia and vitamin D deficiency are both frequent in adult patients. Whether low vitamin D metabolite levels are an independent risk factor for different subtypes of anemia remains to be studied in detail. Methods: In 3299 patients referred for coronary angiography, we investigated the association of 25-hydroxyvitamin D (25OHD) and 1,25-dihydroxyvitamin D [1,25(OH)2D] with anemia [hemoglobin (Hb) <12.5 g/dl] of specific subtypes.Results: Compared with patients with 25OHD levels in the adequate range (50-125 nmol/l), patients with deficient 25OHD concentrations (<30 nmol/l; 33.6 % of patients) had 0.6 g/dl lower Hb levels. Hb values were 1.3 g/dl lower in patients with 1,25(OH)2D levels <40 pmol/l (5.4 % of patients), compared with patients in the highest 1,25(OH)2D category (>70 pmol/l). Of the participants, 16.7 % met the criteria for anemia. In multivariate-adjusted regression analyses, the odds ratios for anemia in the lowest 25OHD and 1,25(OH)2D categories were 1.52 (95 % CI 1.15-2.02) and 3.59 (95 % CI 2.33-5.52), compared with patients with 25OHD levels in the adequate range and patients with 1,25(OH)2D levels >70 pmol/l. The probability of anemia was highest in patients with combined 25OHD and 1,25(OH)2D deficiency [multivariable-adjusted odds ratio 5.11 (95 % CI 2.66-9.81)]. Patients with anemia of chronic kidney disease had the highest prevalence of 25OHD deficiency and 1,25(OH)2D concentrations of <40 pmol/l. Conclusions: Low 25OHD and 1,25(OH)2D concentrations are independently associated with anemia. Patients with poor kidney function are most affected. Interventional trials are warranted to prove whether administration of plain or activated vitamin D can prevent anemia.
Gesehen am 22.11.2018
Published online: 08 January 2016